HARMONISASI ANTARA UU NO 12 TAHUN 1992 TENTANG SISTEM BUDIDAYA TANAMAN DENGAN UU NO 29 TAHUN 2000 TENTANG PERLINDUNGAN VARIETAS TANAMAN: BERLAKUNYA ASAS LEX SPECIALIS DALAM PEREDARAN BENIH TANAMAN - Widiastuti, - (Exsplorasi, 2016)
The lex specialis derogat legi generalis princip must be used when emerged lawdispute . The Rule 29, 2000 about Plant Varieties Protection is one of formalinstitution protected intelecletual property right of bredeers. When the bedeersget intelectual property rights from state, they could not obtain the economicright e.q to copy, export or sell that variety, because the Rule 12, 1992 aboutPlant Cultivation System regulated that the bredeer have to take care of releasedand got seed certificate. The obligations of intelectual property right owner didntmean protection for seeds consumer.Key word : intelectual property right of bredeer, plant cultivation system and seedcertificate